2011
DOI: 10.1111/j.1741-2358.2011.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Oral Impacts on Daily Performance (OIDP) scale in the elderly population of Bosnia and Herzegovina

Abstract: Validity and reliability of the Oral Impacts on Daily Performance (OIDP) scale in the elderly population of Bosnia and Herzegovina Objectives: To adapt the Oral Impacts on Daily Performance (OIDP) index for elderly people in Bosnia and Herzegovina and test its validity, reliability and responsiveness to change. Background: Clinical measures alone may not be adequate for assessing the oral health of individuals. Subjective oral health indicators tested within a particular cultural context may not be relevant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 20 publications
5
25
1
10
Order By: Relevance
“…In this study, Cronbach’s alpha amounted to 0.89 at both measurement occasions and in both countries. This is above the recommended values of 0.70 and consistent with those previously reported in surveys of older people [15,18,19,21,23]. Reproducibility amounted to 0.73 and 0.77 in Norway and Sweden, indicating good stability at both sites [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, Cronbach’s alpha amounted to 0.89 at both measurement occasions and in both countries. This is above the recommended values of 0.70 and consistent with those previously reported in surveys of older people [15,18,19,21,23]. Reproducibility amounted to 0.73 and 0.77 in Norway and Sweden, indicating good stability at both sites [18].…”
Section: Discussionsupporting
confidence: 89%
“…The OIDP has been demonstrated to have appropriate psychometric properties when applied in population based cross-sectional surveys of elderly in Norway, Sweden, Greece and UK, just to mention a few as well as in middle- and low income countries [16-20]. Studies have shown that OIDP is associated in the expected direction with self-reported oral health and clinical indicators and that personal-, socio-demographic-, and health care service related factors modify those relationships [15,18,19,21-24]. Although OIDP has proven appropriate as a discriminative and descriptive measure in cross-sectional studies, there is less evidence on whether this inventory is suitable as an evaluative measure, to assess within individual change in oral health occurring naturally by ageing or as a consequence of interventions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…20.3% of the total population exhibited 21 teeth and over. Restorative needs of at least 1 filling were exhibited by 27.9% 27 .52.5% of the participants in another study in Ankara, Turkey, were edentulous, and tooth loss was more frequent in females compared to males 28 . A possible reason for this observation is that women are more prone to develop osteoporosis, which may have an effect in tooth loss.…”
Section: Resultsmentioning
confidence: 94%
“…Kossioni et al 26 discovered that xerostomia and some other complaints, such as burning mouth, dysgeusia, and oral malodour, were more prevalent in seniors diagnosed with mental disorders than older people without mental disease. 231 free-living individuals aged 65 years and over from Bosnia and Herzegovina were included in a study measuring the validity and reliability of the OIDP (oral impacts on daily performance) scale 27 . 19.9% of the antimuscarinic medicines, some anti-epileptic medicines, some antipsychotics, beta-blockers and diuretics may have a key role in causing dry mouth 17 .…”
Section: Tooth Lossmentioning
confidence: 99%
“…In Asia, the OIDP questionnaire has been used in Thailand, Japan, Korea and China to assess the oral health quality of life of older adults 8,10,12,15 . For preparing a relevant version of OIDP, the English version of the questionnaire was translated to the local Chinese dialect through methods used in earlier relevant studies 6,8,17 . As OIDP measures the most common set of ultimate impacts of oral diseases on daily performances, we were not expecting large content variations in the instrument 5 .…”
Section: Discussionmentioning
confidence: 99%